1993
DOI: 10.1088/0953-2048/6/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapour deposition of high-Tcsuperconducting thin films

Abstract: Fabrication of high-temperature superconducting thin films (Y-Ba-Cu-0, Bi-Sr-Ca-Cu-0, TI-Ba-Ca-CbO systems) by chemical vapour deposition (CVD) is reviewed. The key to the use of the CVD method is to find volatile compounds for the metallic constituents of superconductors. /?diketonate complexes such as acetylacetonates and dipivaloyimethanates have been successfully used as source materials. The quality of the films grown is affected by the deposition temperature, substrate material and postdeposition anneali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(47 citation statements)
references
References 293 publications
2
43
0
Order By: Relevance
“…Similar effect has been noticed in the studies on Er 2 O 3 , where Er 2 O 3 was grown at 250-375 • C from Er(thd) 3 and O 3 [97] and at 175-450 • C from Er(CpMe) 3 [99,105,106]. Praseodymium oxide has been prepared from silylamide precursors and H 2 O [34] and more recently from Pr(mmp) 3 and H 2 O [94]. The films are amorphous, smooth and uniform, without apparent SiO 2 layer formed between Si and metal oxide (Fig.…”
Section: Growth Of Binary Rare-earth Oxide Thin Filmssupporting
confidence: 84%
See 2 more Smart Citations
“…Similar effect has been noticed in the studies on Er 2 O 3 , where Er 2 O 3 was grown at 250-375 • C from Er(thd) 3 and O 3 [97] and at 175-450 • C from Er(CpMe) 3 [99,105,106]. Praseodymium oxide has been prepared from silylamide precursors and H 2 O [34] and more recently from Pr(mmp) 3 and H 2 O [94]. The films are amorphous, smooth and uniform, without apparent SiO 2 layer formed between Si and metal oxide (Fig.…”
Section: Growth Of Binary Rare-earth Oxide Thin Filmssupporting
confidence: 84%
“…Superior performance of La 2 O 3 has been attributed to its wide band-gap and the lowest lattice energy [42]. Jun et al have shown that MOCVD based on La(thd) 3 -tetraglyme results in La 2 O 3 films of slightly higher permittivity and lower leakage compared to La(thd) 3 and La(thd) 3 -TETEA [108]. Besides widely investigated Y 2 O 3 [39], and apart from the Gd 2 O 3 and Ga 2 O 3 studied with the III-V compound substrates [4] as well as Gd 2 O 3 and Sc 2 O 3 in GaN-channel MOSFETs [109], La 2 O 3 and Pr 2 O 3 have become the most frequently studied rare-earth oxide films.…”
Section: Investigation Of Rare-earth Oxides In Mos Capacitors and Mosmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements needed in each process were determined from the process flow schemes given earlier and from literature surveys (20,(40)(41)(42) , which were undertaken to develop a thorough understanding of each process and a comprehensive tabulation of the control parameters. After the process review, a preliminary worksheet for each process was created to provide a general description of the kinds of measurements needed as well as noting the parameter ranges when available from the literature.…”
Section: Process Control Tablesmentioning
confidence: 99%
“…In order to prevent partial crystallization The importance of chemical routes in the preparation of the metal salts we chose complexing agents which conof superconducting materials is well documented for both tained a various number of hydroxo and/or carboxyl bulk and thin-film samples (1)(2)(3). Among the numerous groups, namely, ascorbic acid, citric acid, 1,2-ethanediol studies on high-T c superconducting compounds, those con-(glycol), poly(vinyl alcohol), and succinic acid.…”
Section: Introductionmentioning
confidence: 99%